The Influence of Organizational Culture, Leadership, and Work Environment on Employee Performance with Motivation as an Intervening Variable at the Tax Service Office South Batam Primary - Beny Todo; Mesra B.; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2023)
This research was conducted to test leadership, organizational culture, work environment on employee performance with motivation as mediation. This type of research is causally comparative which shows a causal relationship between one variable and another. The object of this research is the South Batam Pratama Tax Service Office. The data obtained came from the distribution of online questionnaires to 130 employees of the South Batam Pratama Tax Service Office, or also called population. The sampling technique used is a saturated sample, so the number of samples is as many as 130 respondents. Data collection using questionnaires. This research is quantitative type with descriptive data analysis techniques and path analysis processed using Smart PLS software. Based on the results of the study, it was found that the variables of Organizational Culture, work environment, and motivation partially had a positive and significant effect on Employee Performance, while leadership did not affect employee performance. Organizational culture, leadership, and work environment partially have a positive and significant effect on employee motivation. Motivational variables are able to mediate the influence of leadership on employee performance. Motivation is able to mediate the influence of the work environment on employee performance at the South Batam Pratama Tax Service Office.